Unplanned revisits of older patients to the emergency department - Müller, Jenny; Keller, Dagmar I.; Slankamenac, Ksenija (Frontiers in Disaster and Emergency Medicine, 2024)
Introduction Older patients currently represent up to 12%−24% of all emergency department (ED) visits. While increasing in number, they are also at high risk of revisits once discharged. The rate of ED revisits within 72 h is a key indicator of the quality of care in emergency medicine and varies between 1% and 15%. The reasons for ED revisits are natural course of illness, misdiagnosis, lack of homecare, and self-discharge against medical advice. However, the risk factors for ED revisits have not been fully investigated. Therefore, this study aimed to analyze the incidence of ED revisits and identify the risk factors for ED revisits within 72 h after ED discharge. Methods In this retrospective study, older patients (≥70 years) were consecutively enrolled if they presented with an Emergency Severity Index of 2 or 3 in a tertiary care ED in 2019, with discharge after the ED visit. The primary endpoint was the frequency of unplanned ED revisits within 72 h after ED discharge. The secondary endpoints were the reasons and potential risk factors for ED revisits. Univariate and multivariate logistic regression models were used. Results A total of 592 older patients were enrolled, of whom 30 (5.1%) revisited the ED within 72 h. Gastrointestinal diagnosis [odds ratio (OR), 2.9; 95% confidence interval [CI], 1.04–8.2; p = 0.043) and nausea in particular (OR, 3.5; 95% CI, 1.3–9.4; p = 0.016) were significant risk factors for ED revisits. Furthermore, discharge against medical advice (OR, 5.6; 95% CI, 1.7–18.1; p = 0.004) and ED presentation during the night (OR, 2.7; 95% CI, 1.2–6.1; p = 0.014) were significant risk factors for ED revisits within 72 h after discharge, respectively. Conclusion Although the frequency of ED revisits among older patients at 72 h after discharge tends to be low and most revisits were illness-related, all older patients need to be assessed for risk factors for ED revisits. Discharge should be carefully evaluated to improve patient safety and provide the best healthcare to this frail population.